2021
DOI: 10.1017/cts.2021.775
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of health literacy in implementation science

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Subsequently, the improved accessibility of DSME information, led by Diabetes Australia and NDSS, could be a key factor in promoting a more health literate environment in Australia. The improvements in audience reach align with the Australian Commission on Safety and Quality in Health Care, which legislates health literacy for safe and quality healthcare [44], and the ten attributes of organisational health literacy [19]. Audience engagement and reach have been shown to build more enduring and mutually beneficial relationships with the public that can support building trust and strengthening ties with the targeted population [57].…”
Section: Audience Reachmentioning
confidence: 89%
See 3 more Smart Citations
“…Subsequently, the improved accessibility of DSME information, led by Diabetes Australia and NDSS, could be a key factor in promoting a more health literate environment in Australia. The improvements in audience reach align with the Australian Commission on Safety and Quality in Health Care, which legislates health literacy for safe and quality healthcare [44], and the ten attributes of organisational health literacy [19]. Audience engagement and reach have been shown to build more enduring and mutually beneficial relationships with the public that can support building trust and strengthening ties with the targeted population [57].…”
Section: Audience Reachmentioning
confidence: 89%
“…Organisational health literacy is an organisational-wide effort to transform an organisation's delivery of care and services to make it easier for people to navigate, understand and use information and services to care for their health [18]. Seminal work by the Institute of Medicine's Roundtable on Health Literacy identified ten attributes of health literate organisations [19]. Among others, these include leadership that promotes health literacy integral to its mission, structure and operations; co-design; implementation and evaluation of health information and services; culture of innovation; and the distribution of print, audio-visual and social media content that is easy to understand and act on [19].…”
Section: Of 16mentioning
confidence: 99%
See 2 more Smart Citations
“…The role and relationship between health literacy and intervention implementation is multi-faceted and under-researched. A recent review [ 25 ] revealed three key ways in which health literacy features in intervention implementation: (1) in designing and developing interventions, (2) as a contextual factor influencing implementation success, and (3) as an outcome the healthcare intervention [ 25 ]. Overall, however, there is a lack of recognition of the importance of health equity informed implementation of health literacy interventions, and the role that implementation science in facilitating health literacy is under-researched.…”
Section: Implementation Science Intervention Implementation and Healt...mentioning
confidence: 99%